INOVASI PENDIDIKAN ABAD 21 : PENERAPAN PERMAINAN WORDWALL DALAM PEMBELAJARAN BAHASA INDONESIA KELAS XII SMA PGRI 2 PALEMBANG - Ulva Nurma’rifah (JURNAL ILMIAH NUSANTARA, 2024)
21st century education contains education that supports students and liberates students through learning media, both visual and audio. The use of technology as a learning medium can increase students' learning enthusiasm and motivation. One of the learning media that can be used in learning Indonesian in class XII P1.2 historical story text material at SMA PGRI 2 Palembang is the Wordwall game to convey learning material. This research method is descriptive qualitative, namely to tell how the research took place, what was obtained, the factors, results and problems faced by students when learning Indonesian using Wordwall media. Wordwall games have benefits for students and teachers, namely they can increase learning motivation, be more creative, and make it easier for teachers to convey learning material.